(untitled) (The Review of Diabetic Studies, 2024)
The restoration of subgingival cavities presents formidable challenges within dental practice, necessitating a multidisciplinary approach to effectively manage deep marginal elevation techniques (DMETs). This review critically examines the contributions of prosthodontists, endodontists, and restorative dentists in evaluating and implementing DMETs for optimal restorative outcomes. The focus is on the integral roles each specialty plays in addressing the complexities associated with subgingival restorations, particularly in relation to maintaining periodontal health, ensuring functional integrity, and achieving esthetic excellence. Prosthodontists are highlighted for their expertise in assessing clinical indications for DMETs, selecting appropriate techniques based on individual patient needs, and fostering interdisciplinary collaboration to enhance patient outcomes. Endodontists contribute vital insights into the relationship between pulp health and restorative success, significantly impacting treatment planning when managing subgingival cavities. Restorative dentists implement DMETs in clinical practice, engaging directly with material selection and restorative methods, while also considering esthetic demands and functional performance. By synthesizing current literature and clinical practices across these specialties, this review underscores the importance of a cohesive, interdisciplinary framework in restoring subgingival cavities. The examination reveals that effective collaboration among dentists leads to enhanced patient care, improved treatment outcomes, and the promotion of innovative strategies in restorative dentistry. As the field advances, ongoing research into deep marginal elevation techniques, informed by a multidisciplinary perspective, will be vital for meeting the evolving challenges in managing subgingival restorations and ensuring the highest standards of dental care.